A Review of Current Challenges in Production Planning - Szarmes, P. (Acta Technica Jaurinensis, 2015)
For manufacturing companies growing customer expectations, shortening product life cycles and increasing product variant numbers mean great challenges. Overcoming these is a major task for production planning, which is responsible for coordinating all business processes directly related to manufacturing. This paper presents important activities of production planning giving an integrative overview, and presents the digital factory concept with special attention to problems and their possible solutions. It concludes with challenges still waiting to be resolved and future development trends.